2021
DOI: 10.11591/edulearn.v15i2.15985
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between accounting students’ moral development and narcissism on academic fraud

Abstract: The stages in an individual's moral development will determine how an individual will behave. Kohlberg divides moral development into three stages, namely pre-conventional, conventional and post-conventional. However, the stages of individual moral development may vary. These different levels of moral development will influence individuals’ behavior when they face ethical dilemmas. This research aimed to determine the correlation between accounting students’ moral development and narcissism on academic fraud. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Moreover, measurements of deviant or helping behaviours outside the job, such as academic fraud or community prosocial behaviour, were excluded (e.g. Laily et al 2021). Finally, the study did not include samples from prisoners or children, clinical samples or narcissism assessments.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Moreover, measurements of deviant or helping behaviours outside the job, such as academic fraud or community prosocial behaviour, were excluded (e.g. Laily et al 2021). Finally, the study did not include samples from prisoners or children, clinical samples or narcissism assessments.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Beliefs that arise from attitudes to a person towards behavior is called belief behavior (behavioral beliefs) .In addition, the second factor that determines attitude is evaluation results (outcome evaluation). The evaluation results are: personal judgment that the consequences of that behavior taken is liked or disliked (Ajzen, 1997) Preferred consequences of certain behaviors tend to increase a person's intention to do such behavior (Laily et al, 2021). From several definitions of attitude toward the behavior according to some researchers can be concluded that attitude toward the behavior is a behavior that is believed to provide positive results compared to perform a behavior that will give the desired result negative.…”
Section: Attitude Toward Ethical Behaviormentioning
confidence: 99%